Simplifying Homeopathy - Vervarcke, Anne (Homœopathic Links, 2018)
After the initial enthusiasm in the homeopathic community about the exciting progress and expansion since the 1980s, the sobering fact seems to be that we evolved in the direction of such sophistication that our dear system becomes unmanageable. We did our inner work, try to balance things that were somehow off but still the plain fact is that we are still crushed under too much information. And there is no way to stop it! We are only at the beginning of exploring and including every single species on the planet and beyond in our Materia Medica. But we've already come to a point where even the fastest and most extensive software programs won't help us solve a case. In this article, I argue that we need to boil down the overwhelming bulk of data to clear, simple and reliable pointers to large groups and then smaller groups. The best way to do this is adding the ‘context’ in the analysis. Though often overlooked it turns out to be solid information. The first distinction in a case analysis could be between the Second Dimension (Rocks and Stones, Gems, Bacteria, Viruses, Sarcodes) and the Third Dimension groups (Plants, Animal and Fungi) and often the context will decide. Some information on these groups is given, in an attempt to make homeopathy manageable again without losing its refinement.
Keywords: Sophistication and simplicity; Second and third dimensions; Rocks; Gemstones; Sarcodes; Bacteria and viruses; Fungi